2011
DOI: 10.1117/12.879276
|View full text |Cite
|
Sign up to set email alerts
|

A cost-driven fracture heuristics to minimize external sliver length

Abstract: In optical lithography, mask pattern is first fractured into basic trapezoids, and then fabricated by the variable shaped beam mask writing machine. Ideally, mask fracture tools aim at both suppressing the trapezoid count to speed up the write time, and minimizing the external sliver length to improve CD uniformity. However, the increasing transistor density, smaller feature sizes, and the aggressive use of resolution enhancement techniques pose new challenges to write time and CD uniformity. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…3 Many existing fracturing approaches focus on reducing sliver length. 13,14 In addition, Spence et al have demonstrated that the number of shots is directly correlated with the write-time. 5 While there are algorithms which simultaneously minimize sliver number and length along with number of shots, 1, 2 they ignore the underlying physics behind the mask writing process; rather, they solve a simpler geometric partitioning problem by introducing rules to capture the manufacturing parameters.…”
Section: Mask Manufacturing Qualitymentioning
confidence: 99%
“…3 Many existing fracturing approaches focus on reducing sliver length. 13,14 In addition, Spence et al have demonstrated that the number of shots is directly correlated with the write-time. 5 While there are algorithms which simultaneously minimize sliver number and length along with number of shots, 1, 2 they ignore the underlying physics behind the mask writing process; rather, they solve a simpler geometric partitioning problem by introducing rules to capture the manufacturing parameters.…”
Section: Mask Manufacturing Qualitymentioning
confidence: 99%
“…[92,93] formulate this problem to an ILP, and also propose some speed-up techniques. Ma et al [94] present a heuristic algorithm for rectangle fracturing and sliver reduction. Compared to rectangle fracturing, the L-shape fracturing is an effective way to further reduce the number of shots [95][96][97].…”
Section: Ebl Layout Fracturingmentioning
confidence: 99%
“…Recently, Ma et. al [11] presented a heuristic algorithm to generate rectangular shots and further reduce the sliver. Compared with the rectangular fracturing problem, the L-shape fracturing problem is new and there is only limited work, mostly describing methodology, but no systematic algorithm has been proposed so far.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that our algorithms are very promising for both shot count reduction and sliver minimization. In addition, DLF can even achieve significant speed-up compared with previous state-of-the-art rectangular fracturing algorithm [11].…”
Section: Introductionmentioning
confidence: 99%